Bibliometric Analysis of Servant Leadership Research Trends - Mauledy Ahmad (Greenation Research & Yayasan Global Resarch National, 2024)
This study aims to analyze how research on servant leadership in the field of Human Resource Management is classified along with its trends and to find out what topics can be used as research variables in the future. The research method is a literature review using a bibliometric analysis approach starting from defining the keywords 'servant leadership' and 'Journal' in the Publish or Perish application with Google Scholar as a database. After narrowing the results by selecting a special topic in 'Human Resource Management, 840 related articles were obtained to be reviewed from 980 articles of initial search results. Then, I compiled meta data using the Mendeley application. The Vosviewer application was used to visualize research trends. The results showed that the classification of research on servant leadership in human resource management was divided into 7 clusters with topics centred on servant leadership, behaviour, and job satisfaction. Service, development, work engagement, servant leadership characteristics, servant, employee performance, organizational commitment, workplace, Organizational Citizenship behaviour, Turnover Intention and Servant Leadership Behavior are a cluster in the field of Human Resource management. The number and lack of variety of research needed for more review limit this research.